The creation and implementation of advanced practice nursing in France: Experiences from the field. (21st June 2021) - Colson, Sébastien; Schwingrouber, Jocelyn; Evans, Catherine; Roman, Christophe; Bourriquen, Maryline; Lucas, Guillaume; Mellinas, Marie; Brunet, Philippe; Cermolacce, Michel; Chinot, Olivier; Mayen, Sandrine; Berbis, Philippe
Abstract : Aim: This paper describes the characteristics of the new advanced practice nursing roles in France, as well as their challenges and perspectives, and compares the French model with the recommendations of the International Council of Nurses. Background: Advanced practice nursing is particularly well established in English‐speaking countries. Since 2018, France has become the second French‐speaking region to legalize and regulate advanced practice nurses. Source of evidence: The International Council of Nurses and French government websites, and scientific databases (PubMed, CINALH, Cochrane Library) were explored. Feedback from French nursing academics was also requested. Discussion: The advanced practice nursing model in France is described according to the scope and conditions of professional practice. The educational program leads to a State diploma with master's degree, which it is mandatory to be a registered nurse. Remuneration depends on the sector of practice in the public hospital, primary care or private sector. Although there is no national strategy for the implementation of advanced practice nursing roles, research projects are being initiated to guide and evaluate the practice. Based on concordance analysis with the recommendations of the International Council of Nurses, the French advanced practice nursing model appears to be similar to the nurse practitioner model. Conclusion: Adjustments in the scope of practice and education can be expected as the implementation of these roles is evaluated. Implications for nursing practice: This is a historical evolution of the nursing profession in France, for which communication with patients and healthcare professionals is essential. Implications for nursing policy: The implementation of advanced practice nursing roles in clinical settings requires the development of national strategies to support initiatives and ensure the sustainability of these roles.